Algorithmic Mechanism Design With Investment. - Akbarpour, Mohammad; Kominers, Scott Duke; Li, Kevin Michael; Li, Shengwu; Milgrom, Paul (Econometrica, 2023)
We study the investment incentives created by truthful mechanisms that allocate resources using approximation algorithms. Some approximation algorithms guarantee nearly 100% of the optimal welfare in the allocation problem but guarantee nothing when accounting for investment incentives. An algorithm's allocative and investment guarantees coincide if and only if its confirming negative externalities are sufficiently small. We introduce fast approximation algorithms for the knapsack problem that have no confirming negative externalities and guarantees close to 100% for both allocation and investment.